2018
DOI: 10.1016/j.jpainsymman.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Exercise on Cancer-Related Fatigue in Patients With Nasopharyngeal Carcinoma Undergoing Chemoradiotherapy: A Randomized Controlled Trial

Abstract: Context. Tai Chi exercise has been shown to improve cancer-related fatigue (CRF) and autonomic nervous system (ANS) balance in some cancer patients or survivors; however, such effects are yet to be verified in nasopharyngeal carcinoma (NPC) patients undergoing chemoradiotherapy. Objectives. To explore the effects of Tai Chi exercise on CRF in NPC patients undergoing chemoradiotherapy and then to evaluate ANS information indicated by heart rate variability parameters and their association with CRF. Methods. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 37 publications
1
78
0
Order By: Relevance
“…Of 44 full-text articles, 27 were excluded because researchers investigated the acute effects of mind–body exercise ( n = 5), no Tai Chi/Yoga was implemented as the primary intervention ( n = 2), Yoga training took place at a heated environment ( n = 1), non-randomized controlled trials were used ( n = 11), outcome of interest was not reported ( n = 3), children or youth were included as study participants ( n = 2), and resting measure of HRV was not performed ( n = 3). Therefore, we included 17 RCTs in this review [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The process of study selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 44 full-text articles, 27 were excluded because researchers investigated the acute effects of mind–body exercise ( n = 5), no Tai Chi/Yoga was implemented as the primary intervention ( n = 2), Yoga training took place at a heated environment ( n = 1), non-randomized controlled trials were used ( n = 11), outcome of interest was not reported ( n = 3), children or youth were included as study participants ( n = 2), and resting measure of HRV was not performed ( n = 3). Therefore, we included 17 RCTs in this review [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The process of study selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies were published between 2012 and 2018. While 12 RCT involved healthy individuals, five other studies reported people with disease (low back pain, chronic heart failure, nasopharyngeal carcinoma, or fibromyalgia) [ 41 , 50 , 51 , 52 , 53 ]. Sample size (attrition rate from zero to 46.8%) varied greatly across studies, ranging from 26 to 355 (mean age ranged from 25.85 to 71.4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TCC improves vigor in patients with lung cancer undergoing chemotherapy (88). In addition, TCC can alleviate fatigue, enhance neck and shoulder joints mobility, and improves sleep in nasopharyngeal carcinoma patients (89,90). For cancer survivors undergoing chemotherapy, TCC improves cancerrelated fatigue, self-efficacy, and QOL (91).…”
Section: Discussionmentioning
confidence: 99%